A Language for the Specification of the Schema of Spreadsheets for the Materialization of Ontologies - Gómez, Sergio Alejandro (2020)
Ontology-based Data Access (OBDA) is concerned with providing end-users and applications with a way to query legacy databases through a high-level ontology that models both the business logic and the underlying data sources, accessed by mappings that de ne how to express records of the database as ontological assertions. In this research, we are concerned with providing with tools for performing OBDA with relational and non-relational data sources. We developed an OBDA tool that is able to access H2 databases and CSV les allowing the user to explicitly formulate mappings, and populating an ontology that can be saved for later querying. In this paper, we present an extension of our previous work as a language for specifying the schema of the data in a spreadsheet data application. This speci cation is then used to access the contents of a set of Excel books and express them as a relational database with the ultimate goal of materializing its data as an OWL/RDF ontology. We characterize the syntax and semantics of the language, present a prototypical implementation and report on the performance tests showing that our implementation can handle a workload of Excel tables of the order of ten thousand records.